Invasion of Thrips parvispinus (Karny) in Kerala - Anjana S. A.; Thania Sara Varghese; Santhoshkumar T. (Journal of Tropical Agriculture, 2025)
The sucking pest complex is one of the major reasons for the lower production of chilli in India. Recent addition to this pest complexis the invasive thrips, Thrips parvispinus, introduced to India during 2015. A roving survey conducted across Kerala from January to September 2024 confirmed the presence of T. parvispinus in all districts affecting chilli and other horticultural crops. Infestation symptoms included leaf discoloration, crinkling, curling, flower drop and reduced fruit set. Diagnostic characters of T. parvispinus were documented. This study highlights the expanding distribution and host range of T. parvispinus which poses a significant threat to chilli production and other crops in Kerala.